G-jitter fully developed combined heat and mass transfer by mixed convection flow in a vertical channel - Shafie, Sharidan; Amin, Norsarahaida; Pop, Ioan (Elsevier Ltd., 2005)
The effect of g-jitter induced combined heat and mass transfer by mixed convection flow in microgravity for a simple system consisting of two heated vertical parallel infinite flat plates held at constant but different temperatures and concentrations. The governing equations are solved analytically for the induced velocity, temperature and concentration distributions. Graphical results for the velocity profile of the oscillating flow in the channel are presented and discussed for various parametric physical conditions. Despite the simplicity of the problem, it does display some features, which have also been observed in real mixed convection flows, such as flow reversal and flow dependence on the buoyancy parameter ratio